PENINGKATAN KETERAMPILAN MENULIS PESERTA DIDIK KELAS II SDN 01 SUNGAI TALANG DENGAN MENGGUNAKAN MEDIA GAMBAR TAHUN PELAJARAN 2018/2019 - ,, Yetmiwarti (journal of residu, 2019)
Writing skills is one of four language skills that should be mastered by students. The problems which are found in the second grade students of SDN 01 Sungai Talang is the low students? skill in writing, especially writing a sentence. The low of the students? writing skills resulted in the Indonesian language learning outcomes of students are also low. The purpose of this study was to find out how far the improvement of the students? writing skills of second grade students of SDN 01 Sungai Talang using the picture media of the 2018/2019 academic year? This research is Classroom Action Research (CAR), which consists of two cycles. The subjects of this study were second grade students of SDN 01 Sungai Talang which consisted of 13 students. The results of the first cycle of research showed that the percentage of students? mark whose writing skills ?75 was 69%. On the second cycle the percentage of the students' mark of writing skills was 92%. So that it can be concluded that there is an increasing of the students? writing skills to the second grade students of SDN 01 Sungai Talang using the picture media of the 2018/2019